2019
DOI: 10.1002/cncr.31998
|View full text |Cite
|
Sign up to set email alerts
|

Primary care provider–reported involvement in breast cancer treatment decisions

Abstract: Background Treatment decisions for patients with early‐stage breast cancer often involve discussions with multiple oncology providers. However, the extent to which primary care providers (PCPs) are involved in initial treatment decisions remains unknown. Methods A stratified random sample of PCPs identified by newly diagnosed patients with early‐stage breast cancer from the Georgia and Los Angeles Surveillance, Epidemiology, and End Results registries were surveyed (n = 517; a 61% response rate). PCPs were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In a recent study that included 517 women diagnosed with early stage breast cancer, Wallner at al. found that up to one-third of PCPs reported involvement in multimodal breast cancer treatment decisions [15]. Moreover, older PCPs and those who more positively evaluated their ability to participate in cancer treatment decision making were more likely to participate [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study that included 517 women diagnosed with early stage breast cancer, Wallner at al. found that up to one-third of PCPs reported involvement in multimodal breast cancer treatment decisions [15]. Moreover, older PCPs and those who more positively evaluated their ability to participate in cancer treatment decision making were more likely to participate [15].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that after the first intervention, the symptoms of breast pain and swelling in the intervention group were significantly lower than those in the control group. Researchers found that exercise or physical activity not only helps to reduce the symptoms of chemotherapy and digestive tract, but also has a significant effect on breasts and affected limbs of breast cancer patients ( 23 ). Based on this point of view, the perceptual stress reduction control intervention exercises the whole-body muscle to the affected limb.…”
Section: Discussionmentioning
confidence: 99%
“…Survey content was developed based on prior work, modifying measures used by our team on previous surveys, and pilot testing with urologists and PCPs. 3,17,18 PCP Confidence in Treatment Decision-making.…”
Section: Methodsmentioning
confidence: 99%
“…While PCP involvement during survivorship has flourished due to the increasing national emphasis on team-based cancer care delivery, recent research suggests that patients are involving their PCPs during the treatment stage. [1][2][3][4][5] In particular, patients are discussing their initial cancer treatment options with their PCPs in addition to their cancer specialists (e.g., medical oncologist, radiation oncologist, or surgeon). Work by our team found that, in a population-based cohort of women with early-stage breast cancer, over a third of women and their PCPs reported participation by their PCP in their treatment decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation